Effects of carbon-based fillers on thermal properties of fatty acids and their eutectics as phase change materials used for thermal energy storage: A Review. (March 2021) - Al-Ahmed, Amir; Mazumder, Mohammad A. Jafar; Salhi, Billel; Sari, Ahmet; Afzaal, Mohammad; Al-Sulaiman, Fahad A.
Highlights: < Fatty acids (FAs) and FA included-composite PCMs are receiving great attention because of their favored LHS properties > < Low thermal conductivity significantly restricts the preferred utilization of FAs and FA included-composite PCMs > < Carbon-based additives can be used for effective thermal conductivity enhancement of FAs and FA included-composite PCMs > Abstract: Organic phase change materials (PCMs) are the most common heat storage components in latent heat based thermal energy storage (TES) systems. Among the different organic PCMs, fatty acids (FAs) have shown a real potential in important areas, such as, food and medical transportation, passive solar heating and cooling of buildings, etc., because of the suitable thermodynamic and kinetic properties. However, like all other organic PCMs, FAs also suffer from low thermal conductivity (TC) and sometimes seepage issues. Various conducting alien components (metal nanoparticles, metal oxides, etc.) and different carbon-based materials (expanded graphite, graphene, graphene oxide, carbon nanotubes, activated carbon, carbon nanofibers, and carbon black) have been evaluated extensively to enhance the TC. However, carbon-based materials were observed to be superior due to their excellent thermal conductivity, stability, lightweight, and lower cost. While analyzing the literature for this review article, it was found that the bulk of work focuses on FAs, and FAs based composite PCMs with carbon-based fillers and resulting PCMs demonstrated a good performance under the experimental conditions. No obvious discussion exists on the choice of carbon-based filler from a commercial point of view. So, this review attempts to critically evaluate the research work reported to date on the FAs and FA based composite PCMs, where carbon-based fillers have been used. This discussion is followed by comparative analysis to narrow the selection window for specific carbon filler in terms of the best performance.